I am having trouble understanding the solution for this problem: Evaluate $\displaystyle \lim_{n\to\infty} \sum\limits_{i=1}^{n^2} \frac{e^{i/n}}{ne^n}$.

Here's the solution:

$$\lim_{n\to\infty} \sum\limits_{i=1}^{n^2} \frac{e^{i/n}}{ne^n} = \lim_{n\to\infty} \frac{1}{n}\sum\limits_{i=1}^{n^2} e^{i/n-n}=\int\limits_{-\infty}^{0} e^x dx=1$$

How did they get from the Riemann sum to the integral? In other words how is the sum a Riemann sum for $\int\limits_{-\infty}^{0} e^x dx$ ?

  • $\begingroup$ is the summation index n or k ? $\endgroup$ – hamam_Abdallah Jun 28 '17 at 16:06
  • 1
    $\begingroup$ @Salahamam_Fatima Probably neither -- it should be $i$. $\endgroup$ – Clement C. Jun 28 '17 at 16:07
  • $\begingroup$ It is i sorry. I mistyped the problem $\endgroup$ – chrismc Jun 28 '17 at 16:11
  • $\begingroup$ @ClementC. i could be complex. $\endgroup$ – hamam_Abdallah Jun 28 '17 at 16:24
  • 1
    $\begingroup$ There is no need for Riemann sums since $\sum_{i=1}^{n^2}e^{i/n}$ is the sum of a geometric progression, that can be computed in a explicit way. $\endgroup$ – Jack D'Aurizio Jun 28 '17 at 16:30

If you want (or need) to do it as a Riemann sum, your best bet is to change the index of summation, letting $k=n^2-i$, which runs (backwards) from $0$ to $n^2-1$ as $i$ runs from $1$ to $n^2$. Since $i=n^2-k$, we have $i/n-n=(n^2-k)/n-n=-k/n$, so that we get

$$\lim_{n\to\infty}{1\over n}\sum_{k=0}^{n^2-1}e^{-k/n}=\int_0^\infty e^{-x}dx$$

If you really need the result in the form given, you can let $k=i-n^2$ instead, so that $k$ runs from $1-n^2$ to $0$, and write

$$\lim_{n\to\infty}{1\over n}\sum_{k=1-n^2}^0e^{k/n}=\int_{-\infty}^0 e^xdx$$

(Ah, I just now noticed Clement C's comment below the OP, which says exactly the same thing.)

Added later, in response to the OP's question in comments: This is not a standard Riemann sum, in which the interval is fixed and it's just the partition that's getting finer and finer. In this case, $\Delta x={1\over n}$ as usual, but, because $k$ runs from $0$ to $n^2-1$ (in the first displayed equation -- the second one is analogous), $x=k/n$ takes values from $0$ to $n-{1\over n}\approx n$. The upshot is that, for any given (large) $n$, we should (and do) have

$${1\over n}\sum_{k=0}^{n^2-1}e^{-k/n}\approx\int_0^ne^{-x}dx$$

Because it's a somewhat nonstandard Riemann sum, some extra care is technically called for in proving that it converges to the (improper) integral $\int_0^\infty e^{-x}dx$. This is what zhw. does in his/her answer.

  • $\begingroup$ How does this work as the width of each rectangle is (1/n). Shouldn't the limits of integration be 0 to 1 (or some other pair of limits with length 1)? $\endgroup$ – chrismc Jun 29 '17 at 3:34

I did it this way: Define

$$S_n = \sum_{k=1}^{n^2}e^{k/n}\frac{1}{n}.$$

This is a Riemann sum approximating $\int_0^n e^x\, dx.$ Now $e^x$ is increasing. Thus, in the usual way, we can estimate $S_n$ from either side with an integral. Specifically we see

$$\int_0^n e^x\,dx < S_n < \int_{1/n}^{n+1/n} e^x\,dx.$$

The integrals equal $e^n-1$ and $e^{n+1/n}-e^{1/n}$ respectively. Dividing everything by $e^n$ then gives

$$\frac{e^n-1}{e^n} < \frac{S_n}{e^n} < \frac{e^{n+1/n}-e^{1/n}}{e^n}.$$

The limits on the left and right are $1.$ By the squeeze theorem, $S_n/e^n \to 1,$ and this is the desired limit.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.